1967
DOI: 10.1530/jrf.0.0130189
|View full text |Cite
|
Sign up to set email alerts
|

D-Mannitol, Erythritol and Glycerol in Bovine Semen

Abstract: An investigation into the distribution of freely occurring polyhydric alcohols in normal bovine semen has revealed the presence of three previously unreported constituents, namely d-mannitol (17 mg/100 ml), erythritol (6\m=.\9mg/100 ml) and glycerol (circa 2 mg/100 ml). These three polyols, together with inositol and sorbitol were characterized by the preparation of suitable derivatives. Where applicable, the physical constants of the crystalline materials and of their derivatives were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
10
1
1
Order By: Relevance
“…To test the specificity, we studied the growth of WT and Δ eryH in 2YT medium supplemented with polyols (0.1 g/L) with structures close to erythritol ( Supplementary Figure S2 ) that have been reported in male or pregnant female genital organs (Clark et al, 1967; Brusati et al, 2005; Jauniaux, 2005; Regnault et al, 2010; Larose et al, 2012). Since we did not detect any inhibitory effects for glycerol, ribitol, arabitol, xylitol, sorbitol, mannitol or dulcitol, the toxicity was specific for erythritol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the specificity, we studied the growth of WT and Δ eryH in 2YT medium supplemented with polyols (0.1 g/L) with structures close to erythritol ( Supplementary Figure S2 ) that have been reported in male or pregnant female genital organs (Clark et al, 1967; Brusati et al, 2005; Jauniaux, 2005; Regnault et al, 2010; Larose et al, 2012). Since we did not detect any inhibitory effects for glycerol, ribitol, arabitol, xylitol, sorbitol, mannitol or dulcitol, the toxicity was specific for erythritol.…”
Section: Resultsmentioning
confidence: 99%
“…One of the molecular bases that is proposed to account, at least partially, for this tropism is the existence of erythritol in the target organs of ungulates (Smith et al, 1962). Present in substantial amounts in fetal fluids, placenta, seminal vesicles and semen of several ungulate species (Smith et al, 1962; Keppie et al, 1965; Clark et al, 1967), this four carbon polyol promotes Brucella growth at low concentrations and is also a preferred carbon source (McCullough and Beal, 1951; Smith et al, 1962). Bovine fetal tissues that were obtained from 6 to 7 months pregnant cattle (the time after which Brucella abortion often occurs) (Williams et al, 1962) and chorioallantoic membrane explants (Enright and Samartino, 1994) have been described to produce high amounts of erythritol.…”
Section: Introductionmentioning
confidence: 99%
“…In 1967, Clark et al (1967) proposed that this pathway was involved in the production of erythritol, a C4 sugar alcohol they identified among other polyols in bovine semen. This suggests a prominent albeit indirect role for the PP pathway in Brucella genital tropism because previous work not only had shown that erythritol is the preferred carbon/energy source of B. abortus, B. melitensis and B. suis (McCullough and Beal, 1951) but also had reported that it displayed “vitamin-like” properties stimulating the growth of these Brucella spp.…”
mentioning
confidence: 99%
“…in catalytic amounts (Keppie et al, 1965). Since then, the high concentrations of erythritol in fetal fluids, placental tissue, epididymis and semen of the preferred hosts of those Brucella species have been postulated as important in the genital tropism of these pathogens in ruminants (Smith et al, 1962; Clark et al, 1967; Essenberg et al, 2002) and, indeed, recent evidence strongly suggests it is presence in various concentrations in cells and tissues of other Brucella hosts where it was not detected previously (Lowrie and Kennedy, 2001; Burkhardt et al, 2005; Jauniaux et al, 2005). Moreover, speculating on the origin of erythritol in bovine fetal fluids, where it was first identified in animal tissues, Pearce had the insight that: “ it may arise from D-erythrose, a possible product of the pentose phosphate pathway, and act as an intermediate between D-erythrose and D-erythrulose as sorbitol acts as an intermediate between glucose and fructose ” (Pearce et al, 1962).…”
mentioning
confidence: 99%
See 1 more Smart Citation